Spreading behavior of a distilled water droplet on a superhydrophobic surface; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Feoktistov D. V. Dmitriy Vladimirovich (2015, 2015)
Title screen